Gender Differences in Support for Torture. (April 2017) - Lizotte, Mary-Kate
Gender differences regarding support for the use of force average around 8 percent and are twice the size of differences on non-force issues. This article investigates a related gender gap in support for the use of torture. I investigate threat perceptions as a possible explanation for the gap and find strong support for this hypothesis. Specifically, increased threat perceptions lead men but not women to be more likely to support the use of torture. In addition to providing an explanation for the gender gap in support for torture, this extends prior work that finds increased threat perceptions with respect to terrorism lead to greater support for aggressive policies.